Diagnostic value of ex vivo pleural fluid interferon-gamma versus adapted whole-blood quantiferon-TB gold in tube assays in tuberculous pleural effusion - Eman N Eldin; Asmaa Omar; Mahmoud Khairy; Adel H.M Mekawy; Maha K Ghanem (Annals of Thoracic Medicine, 2012)
Background: Noninvasive diagnosis of pleural tuberculosis (TB) remains a challenge due to the paucibacillary nature of the disease. As Mycobacterium tuberculosis (MTB)-specific T cells are recruited into pleural space in TB effusion; their indirect detection may provide useful clinical information. Objectives: Evaluation of pleural fluid interferon (INF)-γ levels vs Quantiferon−TB Gold In tube assay (QFT- IT) in blood and its adapted variants, using pleural fluid or isolated pleural fluid cells in the diagnosis of pleural TB. Methods: Thirty-eight patients with pleural effusion of unknown etiology presented at Assiut University Hospital, Egypt, were recruited. Blood and pleural fluid were collected at presentation for INF-γ assays. Ex vivo pleural fluid INF-γ levels, QFT-IT in blood and its adapted variants were compared with final diagnosis as confirmed by other tools including blind and/or thoracoscopic pleural biopsy. Results: The final clinical diagnosis was TB in 20 (53%), malignancy in 10 (26%), and effusion due to other causes in eight patients (21%). Ex vivo pleural fluid INF-γ levels accurately identified TB in all patients and were superior to the QFT-IT assays using blood or pleural fluid (70 and 78% sensitivity, with 60 and 83% specificity, respectively). QFT-IT assay applied to isolated pleural fluid cells had 100% sensitivity and 72% specificity. The optimal cut-off obtained with ROC analysis was 0.73 for TB Gold assay in blood assay, 0.82 IU/ml for the cultured pleural fluid assay, and 0.94 for isolated pleural cells assay. Conclusion: The ex vivo pleural fluid INF-γ level is an accurate marker for the diagnosis of pleural TB. QFT- IT assay in peripheral blood or its adapted versions of the assay using pleural fluid and/or washed pleural fluid cells had no diagnostic advantage over pleural fluid INF-γ in the diagnosis of pleural TB.